POLICY OF ACCEPTANCE OF STUDENTS WITH DISABILITIES IN INCLUSION SCHOOLS - Sinta Ristiyanti; Muqowim Muqowim (Jurnal Pendidikan (Teori dan Praktik), 2023)
This study aims to describe the provisions in the process of accepting students with disabilities in inclusive schools. This research was conducted with a descriptive qualitative research approach. Data collection was carried out by interview, observation, and documentation techniques. Interviews were conducted with special supervising teachers, counseling teachers, and parents of students with disabilities. Data analysis using the Miles and Huberman technique includes data reduction, data display, and drawing conclusions. The validity of the data was tested by triangulation of sources and techniques. The results of the research show that there are different terms or conditions in the process of accepting students with disabilities in inclusive schools. Therefore, inclusive schools should take in account differences in terms or requirements in the acceptance of students with disabilities.